Effect of abiotic stress on carotenoids accumulation in orange sweet potato calluses under light and dark conditions - Othman, Rashidi; Kammona, Suhair; Jaswir, Irwandi; Jamal, Parveen (2015)
Abiotic stress factors are the main limitation to plant growth and yield in agriculture. Orange sweet potatoes may become major sources of carotenoids in the diet, but the extent of environmental and genetic influences on plant carotenoid biosynthesis are poorly understood. Carotenoid biosynthesis is regulated by several factors such as water, light, pathogen, salinity, nutrients and is susceptible to geometric isomerisation in the presence of oxygen, light and heat which causes colour loss and oxidation. The main problems associated with carotenoid accumulation arise from the inherent instability of pigments. In this study carotenoid biogenesis is investigated in sweet potato callus culture as a potential model system for carotenoids biogenesis by analysing the effects of environmental stress agents such as NaCl (for salt tolerance), PEG (for drought tolerance), salicylic acid (for pathogen stress or disease resistance) and nutrient strength towards carotenoid content and composition. Results of this study revealed that the bioactive compounds detected in orange sweet potato callus were α-carotene, β-carotene, lutein and zeaxanthin. Not surprisingly, the response of sweet potato callus culture to such environments appeared to be highly light dependent. Another factor is the activity of functional enzymes and candidate enzymes that regulate carotenoid biosynthesis which will determine type and quantity of individual carotenoids. By understanding the environmental factors that affected carotenoid biosynthesis, it should be possible to enhance the amount and type of carotenoid that accumulates in sweet potato tubers. In conclusion, in vitro callus culture is suggested as a successful new alternative approaches to enhance or enrich certain carotenoids through controlled environment.